Reviewing Challenges of Drone Technology Application Amongst Contractor G7 - Omar, Mohamad Rizal; Masrom, Md Asrul Nasid; Mohamed, Sulzakimin; Ahamad, Junaidi (Research in Management of Technology and Business, 2022)
Drones are considered a new and innovative technology. Therefore, many fields are showing increasing interest in utilizing drones, such as mapping in mining and surveillance in transportation. The use of drones in the field of construction is relatively less. Malaysian construction industry still suffers with many problems and being associated with low quality, low productivity, unskilled, project delays, poor maintenance, non-conducive and high accident rates. Even though challenges faced by the construction industry in construction stage are always being widely studied, there are still inadequate studies that provide an overview of issue regarding the using of drone in Malaysia construction industry. Thus, this research aims to study the application of drone in construction, the challenges of the drone implementation and solution to resolve challenges faced by contractor G7. The approach of this study which is qualitative method by doing interviews with seven respondents representing seven different G7 company that located in Klang Valley (Selangor & Wilayah Persekutuan Kuala Lumpur). The data receive from the respondents are analysed using thematic analysis method. The results of this study expressed that drone are most implemented in construction to help reporting purposes. Besides, the most common challenges revealed by this research are technical knowledge. Proper planning and training either provided by the company or authorities are necessary to resolve the challenges. Therefore, all parties including government, company/workers, personnel shall take initiatives to resolve the challenges faced